Seasonal dynamics and activity of typical freshwater bacteria in brackish waters of the Gulf of Gdańsk. (3rd May 2013) - Piwosz, Kasia; Salcher, Michaela M.; Zeder, Michael; Ameryk, Anetta; Pernthaler, Jakob
Abstract : While typical freshwater and marine bacteria have been found to co‐occur in brackish habitats, it is unknown if they are active members of the local bacterial assemblages or if their presence is the result of passive transport only. We followed the seasonal dynamics of typical freshwater bacteria (R‐BT lineage of Betaproteobacteria ; Ac1 Actinobacteria ; LD12 Alphaproteobacteria ) and of marine SAR11 Alphaproteobacteria in the brackish water of the Gulf of Gdańsk (southern Baltic Sea), and we assessed their incorporation of thymidine and leucine at three distinct environmental conditions. The temporal development of bacteria was driven not only by local conditions but also by phenomena resulting from the dynamic hydrology of the site. Both temperature and salinity were important factors influencing bacterial community composition, as reflected by the clear distinction of three assemblages in spring and summer and during a period of enhanced freshwater influx. During spring, high proportions of R‐BT Betaproteobacteria and Ac1 Actinobacteria incorporated the radiolabeled tracers, and all three freshwater lineages were most active during the subsequent phase of low salinity. The summer period was characterized by highest abundances of Ac1 Actinobacteria and of both alphaproteobacterial lineages. All studied freshwater lineages were active members of the brackish water communities at specific environmental conditions, including LD12 Alphaproteobacteria, which have so far been considered to thrive exclusively in freshwater habitats. By contrast, the presence of the typical marine SAR11 bacteria seemed to result from passive inflow with more saline waters from the Baltic proper.